STRATEGIC HUMAN RESOURCES PLANNING IN EDUCATIONAL INSTITUTIONS (Third Sector Social Economic Review, 2024)
This study examines strategic human resource planning in educational institutions. A literature review was conducted and relevant national and international publications were reviewed. This quantitative research collected and analyzed data using scales in order to examine the relevant variables in the best way. In the study conducted with 403 participants, the ""Strategic Human Resources Management Practices"" section of the scale prepared by Kaçmaz (2015) was utilized. At the end of the study, it was determined that the participants working in private schools scored higher in the HR planning sub-dimension than those working in public schools. This may suggest that HR planning in private schools is more effective and teachers are more satisfied with it. In addition, in the sub-dimensions of motivation and retention of HR, it was observed that the participants working in public schools scored higher than those working in private schools. This may suggest that HR strategies in public schools are effective in increasing teacher satisfaction and that teachers working in public schools tend to keep their jobs longer. In general, given that teachers scored higher than administrators in the sub-dimensions of strategic HRM practices, HR planning, remuneration, rewarding, motivation and health and job security, it can be said that teachers have a more positive perception of HRM policies. In addition, the analysis revealed that there is a relationship between strategic approach to HRM and strategic HRM practices. Accordingly, there is a positive and moderate relationship between the strategic approach to HRM and strategic HRM practices and between the HR Retention and Job Security sub-dimension, and a positive and weak relationship between the other sub-dimensions.
Keywords: Educational Institutions; Human Resources; Planning